Sistem Informasi Tim Penggerak PKK Kelurahan Tambangan Berbasis Website - Tri Devi Anti; Novita Mariana (Elkom : Jurnal Elektronika dan Komputer, 2022)
Tambangan Village is one of the urban villages in Semarang City that is active in managing PKK so that it has received several awards in managing the PKK program at both the city and provincial levels. The administrative process in Tambangan Village still uses manual methods both in data recording and recapitulation. This causes several problems that often become obstacles in the PKK administrative process in Tambangan Village, namely there is often scattered data, writing errors, recapitulation of the amount of data that is less accurate and the reporting process is complicated, causing the administrative process to take a long time and information that is incomplete. produced less accurate and inappropriate in the field. This study aims to create a PKK information system in Tambangan Village that can be used to manage data and information for dawis groups, PKK members, PKK activities, the presence of PKK members and Posyandu activities. The results of the questionnaire test from the use of the PKK information system that was built were measured using a Likert scale and the results were 92% with a very satisfied category.